Meningkatkan Kemampuan Memahami Kata dan Kalimat Aksara Jawa Bersandhangan Melalui Media Monopoli Aksara Jawa pada Siswa Kelas VA SD Muhammadiyah Karangkajen 2 Yogyakarta - Rosma Savitri (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This research aims to improve the ability to understand Javanese aksara in conjunction with the Javanese script monopoly media in VA students of Muhammadiyah Elementary School Karangkajen Yogyakarta. This research is a Kelass Action Research (PTK) using the Hopkins model which consists of two cycles. The subjects of this study were 26 grade VA students of Muhammadiyah Elementary School Karangkajen Yogyakarta. This research took place in October 2018, in the odd semester of the 2018/2019 academic year. Data collection techniques in this study are test and observation activities during the learning process. The data analysis technique used in this research is quantitative descriptive. The data from the research shows that the use of Javanese script monopoly media in learning Javanese can improve the ability to understand Javanese scripts with the same language. The use of these media can attract students attention and motivate students so that learning outcomes increase. This can be seen from the increasing transliteration of Javanese script into Latin writing and vice versa. In the pre-cycle, the number of students who reached KKM were 2 students or 8% to 15 students or 58% in the first cycle and increased to 25 or 96% in the second cycle.